Dopplervelocimetria da artéria oftálmica em mulheres na perimenopausa e pós-menopausa usuárias de terapia hormonal - Saramago, Ana Luíza Pereira (2019)
Background: The vascular endothelium has specific estrogen receptors and the impact of hormone therapy (HT) on circulation is associated with cardiovascular protection in perimenopause and postmenopause. Blood vessels can be assessed by ultrasound Doppler velocimetry, and more specifically, the study of the ophthalmic artery can be used for brain vessel assessment, and more recently, a possible method for cardiovascular risk assessment. Methods: We performed a cross-sectional study with peri and postmenopausal women; divided into three groups: 60 non-HT users (control group), 23 estrogen therapy users (ET group) and 23 estrogen-progesterone therapy users (EPT group). Doppler velocimetry of the ophthalmic artery (OA) was performed with the evaluation of: resistance index (RI), pulsatility index (PI), peak systolic velocity (P1), second peak systolic velocity (P2), peaks velocities ratio (PVR), end-diastolic velocity (EDV) and ratio of systolic and diastolic velocity means (RSD). Results: There was no significant difference between the groups in Doppler velocimetry indices of OA. We observed a positive correlation of RSD with age only in the control group (r = 0.34, p = 0.01). Conclusions: There is a positive correlation between RSD and age in the control group. Therefore, this new index is a promising instrument in the noninvasive assessment of cardiovascular risk.